Die AfD in den Landtagen: Bipolarität als Struktur und Strategie – zwischen Parlaments- und ,,Bewegungs“-Orientierung - Wolfgang Schroeder; Bernhard Weßels; Alexander Berzel (Zeitschrift für Parlamentsfragen, 2018)
Before making it into the Bundestag in 2017, the party “Alternative für Deutschland”(AfD) had been present in 13 state parliaments. This study focuses on the AfD parliamentary groups profiles, on AfD's parliamentary performances and the impact they have on their respective parliaments as well as on how the representatives of the other factions in parliament deal with AfD's presence. These questions are investigated on the basis of official and otherwise published materials, information on parliamentary activities, and, in particular, expert interviews with representatives of the AfD and of other parties in parliament. Two divergent orientations can be found among the state parliament AfD factions: On the one hand parliament-centered, on the other “movement” oriented. Whether strategically designed or not – currently this bipolarity ensures both the electoral success and the parliamentary presence of the AfD. Political professionalization is very much at an early stage. Instead of emphasizing the committee work, the AfD relies heavily on the parliamentary plenum as a platform for its public relations primarily via social media.
Keywords: 330